Pilot Study on the Profiling and Functional Analysis of mRNA, miRNA, and lncRNA in the Skeletal Muscle of Mongolian Horses, Xilingol Horses, and Grassland-Thoroughbreds - Wenqi Ding; Wendian Gong; Tugeqin Bou; Lin Shi; Yanan Lin; Huize Wu; Manglai Dugarjaviin; Dongyi Bai (Animals)
Muscle fibers, as the fundamental units of muscle tissue, play a crucial role in determining skeletal muscle function through their growth, development, and composition. To investigate changes in muscle fiber types and their regulatory mechanisms in Mongolian horses (MG), Xilingol horses (XL), and Grassland-Thoroughbreds (CY), we conducted histological and bioinformatic analyses on the gluteus medius muscle of these three horse breeds. Immunofluorescence analysis revealed that Grassland-Thoroughbreds had the highest proportion of fast-twitch muscle fibers at 78.63%, while Mongolian horses had the lowest proportion at 57.54%. Whole-transcriptome analysis identified 105 differentially expressed genes (DEGs) in the CY vs. MG comparison and 104 DEGs in the CY vs. XL comparison. Time-series expression profiling grouped the DEGs into eight gene sets, with three sets showing significantly up-regulated or down-regulated expression patterns (p < 0.05). Additionally, 280 differentially expressed long non-coding RNAs (DELs) were identified in CY vs. MG, and 213 DELs were identified in CY vs. XL. A total of 32 differentially expressed microRNAs (DEMIRs) were identified in CY vs. MG, while 44 DEMIRs were found in CY vs. XL. Functional enrichment analysis indicated that the DEGs were significantly enriched in essential biological processes, such as actin filament organization, muscle contraction, and protein phosphorylation. KEGG pathway analysis showed their involvement in key signaling pathways, including the mTOR signaling pathway, FoxO signaling pathway, and HIF-1 signaling pathway. Furthermore, functional variation-based analyses revealed associations between non-coding RNAs and mRNAs, with some non-coding RNAs targeting genes potentially related to muscle function regulation. These findings provide valuable insights into the molecular basis for the environmental adaptability, athletic performance, and muscle characteristics in horses, offering new perspectives for the breeding of Grassland-Thoroughbreds.